Formulation development and in vitro evaluation of gastroretentive hollow microspheres of famotidine - Chordiya, Mayur A; Gangurde, Hemant H; K, Senthilkumaran; Kothari, Lokesh P (International Journal of Pharmaceutical Investigation)
Background: The main aim of this study was to develop a gastroretentive, multiple-unit floating drug delivery system for a drug which is poorly absorbed from the lower gastrointestinal tract. Such a dosage form may provide an extended retention of drug in the upper gastrointestinal tract resulting in enhanced absorption and improved bioavailability. Materials and Methods: Microspheres were prepared by the emulsion solvent diffusion method. Four different ratios (1:1, 1:2, 1:3, and 1:4) from each polymer, i.e., Eudragit RL 100 (E1–E4) and cellulose acetate (C1–C4) were prepared. Results: Hollow microspheres were characterized by particle size using optical microscopy. The in vitro release data obtained for the formulations E1–E4 and C1–C4 showed good entrapment efficiency, good percentage buoyancy, and prolonged drug release. The in vitro drug release showed the highest regression coefficient values for Higuchi’s model, indicating diffusion to be the predominant mechanism of drug release. The surface and cross-sectional morphology of the formulations E1-A and C1-A were determined using scanning electron microscopy. Conclusions: Thus, prepared floating hollow microspheres of famotidine may prove to be potential candidates for the multiple-unit drug delivery device adaptable for any intragastric condition.
Keywords: Cellulose acetate; emulsion solvent diffusion; Eudragit RL 100; Higuchi’s model; scanning electron microscopy